A model for target acquisition and edge detection under complex scenes. (24th October 2019) - Wang, Fei; Zhu, Jihong
For the needs of target acquisition and edge extraction under complex scenes, a method based on layer by layer segmentation is proposed. First of all, morphological reconstruction technology is combined with ant colony edge detection method to execute pre-segmentation to get the foreground that targets locate. Secondly, line scanning technique is used to divide foreground into several parts for further segmentation. And then, mean difference characteristic is adopted to determine seed point, with which region growing algorithm is applied to find true targets. Finally, active contour method is used to find out the edge of targets. The experimental results show that our method is effective in finding the target and extracting its edge under complex scenes.